Formation of ornamental traditions in ukrainian folk weaving (Pedagogy of Higher and Secondary Education, 2009)
Are considered istoriko-etnichexkie aspects of formation of ornamental traditions in the Ukrainian national weaving.
Keywords: national weaving; ornament composition; ornamental motives; colouraria decision